REMEDIASI MISKONSEPSI SISWA MENGGUNAKAN STRATEGI KONFLIK KOGNITIF BERBANTUAN SIMULASI PHET TENTANG RANGKAIAN LISTRIK DI SMA - Yusran, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research aimed to determine the effectiveness of cognitive conflict strategy assisted by PhET Simulation to remediate students’ misconception on DC electric circuits. A total 35 students were selected from class XI IPA 1 SMAN 1 Teluk Keramat by using intact group random sampling technique. The research design in this study using one group pretest-posttest design. Data was collected by using the diagnostic tests in the form of multiple-choice with open reasoning comprised of 18 questions by representing three concepts related to DC electric circuits. The result shows that average of decrease in number of students’ who have misconceptions for each concepts were 53,33% with a significance of decrease by McNemar test is (47,27) > (3,84). Therefore, it can be conclude that the decrease in number of students’ who have misconception before and after remediation is significant. The effectiveness of remediation by using cognitive conflict strategy assisted by PhET Simulation is 0.67 (medium). This research is expected to be used as reference for teachers to remediate students’ misconception. Keywords: Remediation, Conflict Cognitive, PhET Simulation